Modeling and optimization of supercritical fluid processes - Díaz, María Soledad (2008)
In this work, we discuss recent advances on thermodynamic modeling, process simulation and optimization of supercritical extraction and fractionation processes. The increasing availability of experimental data, as well as the need for estimation of economical viability, has encouraged the development of supercritical processes computer models. This review will discuss main approaches on phase equilibrium thermodynamic modeling of high-pressure processes, as well as process simulation. In this case, two main supercritical processes are considered: extraction of valuable products from solids and countercurrent fluid–fluid extraction and fractionation. In the latter process, again two main approaches are considered: rigorous models based on equilibrium stages and mass transfer models in packed columns. Finally, optimization procedures will be reviewed, both based on rigorous models and on experimental data.